2020
DOI: 10.1155/2020/3897427
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Practice and Associated Factors among Mothers of One-Month-Old Infants in Southwest Ethiopia

Abstract: Newborn care refers to the care that is provided to the baby from birth to one-month-old by a caregiver or by the mothers including thermal care, hygienic care, cord care, eye care, breastfeeding, immunization, and identification of newborn danger signs. According to Ethiopian Demographic and Health Survey (EDHS) 2016, the neonatal mortality rate was 29 deaths per 1000 live births, and the postneonatal mortality rate was 19 deaths per 1000 live births with neonates contributing 48 deaths per 1000 of the infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 11 publications
(26 reference statements)
5
26
2
Order By: Relevance
“…Keeping the cord clean and dry without application of any foreign substances until the umbilical stump falls off (until 7 days of life) ( 23 ). In this study, the mother's cord care was classified as clean when it was kept dry and free of any foreign substances; other forms of treatment to the umbilical cord stump were classified as unclean, including the use of butter, herbs, salt, oil, and Vaseline ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Keeping the cord clean and dry without application of any foreign substances until the umbilical stump falls off (until 7 days of life) ( 23 ). In this study, the mother's cord care was classified as clean when it was kept dry and free of any foreign substances; other forms of treatment to the umbilical cord stump were classified as unclean, including the use of butter, herbs, salt, oil, and Vaseline ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the current meta-analysis, five studies [ 25 , 32 , 39 , 40 , 42 ] reported that women who attended primary education and above were significantly associated with the practice of ENC. The pooled odds ratio indicated that women who attended primary education and above were seven times (AOR = 7.08, 95% CI 4.79, 10.47) more likely to practiced ENC.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, seven studies [ 20 , 22 , 23 , 25 , 34 , 41 , 42 ] revealed that women who had good knowledge of ENC were nearly three times (AOR = 2.93; 95% CI 1.81, 4.75) more likely to practice ENC practice when compared with those women who had poor knowledge of ENC. The heterogeneity test showed that (I 2 = 82.4%, P < 0.001) hence, the random-effect model was used for analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Those mothers who had correctly practised more than or equal to three essential newborn cares were coded as a good practice and less than three were coded as a poor practice. 20 …”
Section: Methodsmentioning
confidence: 99%